2004
DOI: 10.3390/mca9020275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Periodic Magnetic Field to the Dynamics of Vibrating Beam

Abstract: Dynamics of a magnetoelastic beam in a periodic magnetic field is investigated. For this aim, a new measurement tool for the observation of vibrations of the beam is introduced in place of Using common strain-gauge technique. Several analyses including power spectra, maximal Lyapunov exponent, correlation dimension and time series clustering are carried out to determine vibrational aspects of the system. As a result of these analyses, it is found that the system extremely depends on the frequency of external f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It was not possible to obtain experimental results for every value of γ from the experimental point. Here, we will not give the details about the results of the experimental studies, meanwhile we would like to present a representative output in the case of f = 10 and γ = 2.61 (for more details see [16]). In Figures 9a and b, the corresponding time series from our numerical and experimental studies are shown, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not possible to obtain experimental results for every value of γ from the experimental point. Here, we will not give the details about the results of the experimental studies, meanwhile we would like to present a representative output in the case of f = 10 and γ = 2.61 (for more details see [16]). In Figures 9a and b, the corresponding time series from our numerical and experimental studies are shown, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Exponents equal to either 0 or negative values toward the periodic region. In one of our earlier studies, we also carried out an experimental research on this system [16]. In the experimental process a new tool, which consists of a laser-deduction mechanism was introduced for the measurement of the vibrations.…”
Section: Resultsmentioning
confidence: 99%
“…It was proved [21,22] that an electromagnet could create a static and inhomogeneous magnetic field near the tip of the magnetoelastic beam. The dynamics of the pendulum-like beam consists of a certain elastic force, gravitational force and magnetic force.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The damping coefficient is proven to be important in order to characterize such a harvester system. The effects of excitation frequencies in terms of even and odd values are undeniable in the sense that the system generates much complexity for odd frequencies (see in [21]). In addition, the intermediate regimes of two-well chaos persist for appropriate parameter sets such as the magnetic field magnitude and excitation frequency.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation